Reconfigurable-Rate Product Decoders for Rate-Adaptable Optical Networks - Jain, Vikram (My University, 2018)
Optical communication systems use forward error correction (FEC) to reduce the bit-error rate (BER) of the received information bits. The legacy optical links were designed to operate at fixed data rate and never changed parameters during the course of their operation. However, recently rate-adaptable optical systems which can vary parameters over time have gained considerable attention in the research community. These systems can vary their parameters based on the traffic requirements or operator decision. To cater to such systems, FEC schemes which can vary code rate and coding gain are required. For example, if the transmission channel noise is low, lower coding gain is required which means that the code rate can be increased. In this work, we introduce a multi-rate product decoder that can operate in different modes governed by the code rate and the decoding iterations. The implemented multi-rate product decoder provides an estimated net coding gain range of 9.96–10.46 dB at a post-FEC BER of 10−15. The decoder is synthesized in a 28nm FD-SOI process technology and provides high throughputs in excess of 300 Gbps, reaching 1.6 Tbps for one mode of operation. It also exhibits very low decoding latencies of below 100 ns for all modes of operation. With an efficient clock gating strategy, the power dissipation incurred is below 1Wwhich corresponds to an energy dissipation per information bit of 1.5 pJ/bit.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science